MAIN FACTORS IN THE DEVELOPMENT OF RELIGIOUS AND PSYCHOLOGICAL IMMUNITY IN YOUTH (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article deals with the formation of religious-psychological immunity as a principle of peace and stability, which is a fundamental principle of world religions. In the conditions of global challenges faced by mankind, this principle acquires special significance. Also in the article the factors of formation of religious-psychological immunity and practical measures to strengthen religious-psychological immunity are given.